Living the Opposite Sex Trans Journeys in Southern Spain - Imhof, Christoph (Kultur und soziale Praxis, 2022)
Studying the life situations of trans persons reveals preceding and ongoing political, societal and cultural transformations. This ethnographic study concerns individuals in Andalusia, Southern Spain, who do not fit the sex and gender assigned to them at birth. Christoph Imhof thus investigates issues leading back to the repressive situation during the dictatorship of Franco and to contemporary endeavours and achievements regarding acceptance, citizenship and self-determination. He highlights the pioneering role that Andalusia has played within Spain regarding trans issues since the late 1990s and shows how trans persons in Southern Spain have experienced the growing social, medical and legal acceptance of their gender non-conformity.